2012
DOI: 10.7314/apjcp.2012.13.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Hyperthermic CO2Pneumoperitoneum on Human Gastric Cancer Cells

Abstract: Aim: To elucidate the effects of hyperthermic CO 2 pneumoperitoneum on human gastric AGS cells. Methods: Based on a newly devised in vitro study model, we evaluated the anti-cancer effects of HT-CO 2 (42-44˚C for 2-4h) on human gastric cancer cells, and also the corresponding mechanisms. Results: HT-CO 2 (42-44˚C for 2-4h) severely inhibited cell proliferation as assessed by Cell Counting Kit-8 assay, while inducing apoptosis in a temperature-and time-dependent manner demonstrated by annexin-V/PI flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The exposure of tumors to hyperthermic conditions has been revealed to be an effective adjuvant therapy to radiotherapy and chemotherapy for a range of cancers, including locally advanced head and neck cancer (1), melanoma (2), esophageal cancer (3,4), locally advanced cervical cancer (5) and gliomas (6). These results suggest that hyperthermic conditions confer a beneficial effect during laparoscopic resection of gastric cancer (5). CO 2 pneumoperitoneum is used in laparoscopic surgery for the creation of an operative field.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The exposure of tumors to hyperthermic conditions has been revealed to be an effective adjuvant therapy to radiotherapy and chemotherapy for a range of cancers, including locally advanced head and neck cancer (1), melanoma (2), esophageal cancer (3,4), locally advanced cervical cancer (5) and gliomas (6). These results suggest that hyperthermic conditions confer a beneficial effect during laparoscopic resection of gastric cancer (5). CO 2 pneumoperitoneum is used in laparoscopic surgery for the creation of an operative field.…”
Section: Introductionmentioning
confidence: 85%
“…CO 2 pneumoperitoneum is used in laparoscopic surgery for the creation of an operative field. Previous data has revealed that compared with ambient temperature CO 2 , hyperthermic CO 2 (HT-CO 2 ) pneumoperitoneum directly inhibits cell proliferation and induces cell apoptosis in gastric and colorectal cancers (5,6). However, the oncological effect and underlying mechanism of HT-CO 2 on tumor immune responses remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that thermotherapy can enhance the efficacy of radiotherapy through its complementary effect on radiotherapy (Cui et al, 2012), direct effect on tumor cells (Wang et al, 2012;Zhou et al, 2012) and regulation of immune function. Thermotherapy targets cell membrane and cytoskeleton, while radiotherapy targets DNA, so the combined treatment can exert synergistic effect from different mechanisms (Saga et al, 2002;Bottaro and Liotta, 2003;Griffin et al, 2010;Dings et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The use of CO 2 can be beneficial and add an oncological effect. An experimental study by Zhou et al [26] demonstrated that adding a CO 2 pneumoperitoneum at 15 mmHg and 42-44 for 2-4 h induced a cytotoxic effect on gastric cancer cells induced by Bax protein, causing apoptosis. Ma et al [27] also observed a decrease in adhesion molecule expression (E-cadherin, ICAM 1, CD44 and E-selectin) in colon cancer cells after an infusion with CO 2 at a pressure of 15 mmHg, both in vitro and in vivo.…”
Section: Control Of Intra-abdominal Pressurementioning
confidence: 99%